Comportamiento del Gammaclobulina de la saliva y suero de pacientes infectados con el virus del Sida, y su relación con la patología bucal - Taboada Vega, Manuel (2003)
The present ínvestigation íncluided: 100 samples, 20 control groups (Universidad NAcional Agraria students), and 80 patients infected with HIVIA1DS; 25 with level 11, 35 with level III, and 20 patients with level /V Average proteinicfractions and salivary percentage were taken: Albumin 45.15%, SALIVARYALBUMIN 15.2%, GAMMAGLOBULIN 7-5.94% (SIGNIFICANCE LEVEL 1.00%).Problem Sample. - In the problem sample we can see a considerable alteration in the serical electropitoretics proteins. Spit: level 11, 22.12% albumin, gammaglobulin 77.64%, level III, albumin 16.35%, gammaglobulin 83.49%. IV 7.71% albumin and 92.37% gammaglobulin. There is a diferrential relationship between normal values of serical gammaglobulin and salivary ones, in HIV/AIDS ínfected patiens and there is an increase of bucal pathologies